2021
DOI: 10.18280/acsm.450605
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Marble Waste as Powder and Aggregate Form on the Proprieties of the Mortar

Abstract: Recycling and recovery of waste are now considered as a solution for the future to protect the environment. The marble processing workshops on the other hand, generate a large amount of waste in the form of powder and small parts. Due to these facts, the aim of this study is to valorize marble waste in the form of powder and crushed aggregates (sand) as additions in cementitious matrix building materials. The characterization of the materials used to formulate mortars based on natural dune sand with marble pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Currently, the disposal of marble waste is a matter of concern for both environmentalists and manufacturers [4,5]. Numerous attempts have been made to repurpose marble waste as aggregate [1,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the disposal of marble waste is a matter of concern for both environmentalists and manufacturers [4,5]. Numerous attempts have been made to repurpose marble waste as aggregate [1,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The most results demonstrated that samples activated with Na2SiO3 presented the best compressive strength between 1-28 days in ambient temperature [13]. There is also another parameter that controls the role of the material after it is entered into a mixture, which is the specific surface or fineness [16,17]. For Cyr et al, [18] utilized one part of glass powder with fineness between 100-400 m 2 /kg and three parts of sand to build geopolymer mortars, the source of glass it is just derivative from recycled bottles.…”
Section: Introductionmentioning
confidence: 99%